Amperometric Immunosensor for Chagas' Disease Using Gold CD-R Transducer - Foguel, Marcos Vinicius [UNESP]; dos Santos, Glauco Pilon [UNESP]; Pupim Ferreira, Antonio Aparecido [UNESP]; Yamanaka, Hideko [UNESP]; Benedetti, Assis Vicente [UNESP] (Wiley-Blackwell, 2011)
Chagas' disease has been spread mainly through blood transfusion or blood components, therefore the development of a device for neglected diseases with high specificity and sensitivity is important to public health. This work describes the development of an amperometric immunosensor for determination of Chagas' disease through a gold-based electrode obtained from a recordable compact disc modified with 4-(methylmercapto) benzaldehyde for the immobilization of Tc85 protein of the Trypanosoma cruzi. The immunoassays were carried out using positive and negative sera from Chagas' disease patients and immunoglobulin conjugated with peroxidase enzyme. The immunosensor presented -0.949 mu A as cut-off value and was applied in sera samples.
Keywords: Chagas' disease; Gold CDtrodes; Immobilization; Self-assembled monolayer; Sensors